PHASE AMBIGUITY REDUCTION IN LASER INTERACTED INTERFEROGRAMS - Yahaya, Asiah; Munajat, Yusof (2006)
Phase measurement of laser interaction is often plagued with ambiguity when analyzed using single interferogram. This ambiguity is often due to the existence of extra fringes in the area of disturbance of acoustic wave propagation by laser interaction. A new 3-interferograms phase measurement interferometry system incorporated with quadrature technique was developed to reduce this problem. The interferograms were initially shifted by 90º phase difference, a condition for quadrature imaging. Three interferograms of laser interaction with a single pulse of Nd:YAG laser were captured by three CCD cameras simultaneously, with dye laser as a flash illuminator. An appropriate algorithm utilizing intensity distributions, matched pixel to pixel was able to reduce the problem. It was found that the maximum phase change was (2.5 ± 0.1) rad for an interaction of a 3 mJ Nd:YAG laser pulse at a delay of 3.6 µs. This phase change profile can be used in the analysis of pressure profile of laser interaction by Abel inversion technique.